2009
DOI: 10.1007/s11802-009-0233-3
|View full text |Cite
|
Sign up to set email alerts
|

Fishery resources in arid zone mangroves in gulf of Kachchh, Gujarat, northwest coast of India

Abstract: The finfish and shellfish resources were assessed quantitatively and qualitatively in regard to their abundance in creek waters at three sites within a period of two years, from January 1999 to December 2000, in the western mangrove areas of Kachchh. The catch rate varied from 0.69 to 6.99 kg h -1 . It was low during monsoon (July to October), which could be due to the freshwater-flow-induced salinity reduction in all the sites. Among 38 species recorded, 5 were shellfish and 33 were finfish. The spawning peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For instance, in some states in eastern part of India such as Andhra Pradesh, the ponds are filled with borehole water mixed with estuarine water, which causes the salinities of the grow-out ponds to fluctuate between 0 and 30 ppt with an average salinity of about 10 ppt. In contrast, in states located in the western part of the country such as Gujarat, salinities in pond water may vary between 30 and 44 ppt [ 10 , 11 ]. In Venezuela on the western hemisphere, the shrimp farms are located in two areas.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in some states in eastern part of India such as Andhra Pradesh, the ponds are filled with borehole water mixed with estuarine water, which causes the salinities of the grow-out ponds to fluctuate between 0 and 30 ppt with an average salinity of about 10 ppt. In contrast, in states located in the western part of the country such as Gujarat, salinities in pond water may vary between 30 and 44 ppt [ 10 , 11 ]. In Venezuela on the western hemisphere, the shrimp farms are located in two areas.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually found in the northern Indian Ocean and west Pacific waters (Saravanakumar et al, 2009) and are important economic fishes of the coastal waters in China Sea, occupying an important position in the offshore fishing of China (Du and Huang, 2009). The two species are both important feed fish.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study area of Pondicherry coast has natural environmental handicaps as a result from its isolated position, and several manmade stresses are considered to be mainly responsible for a decline of molluscs. Since coastal ecosystems are responsible for a large amount of fish and shellfish yields, Saravanakumar et al (2009) had reported the baseline information of fin and shellfish resources and abundance, that would form a useful tool for further ecological assessment and monitoring of this coastal mangrove ecosystem.…”
mentioning
confidence: 99%